BDNF as a Biomarker of Cognition in Schizophrenia/Psychosis: An Updated Review - Nieto, Rodrigo R.; Carrasco, Andrea; Corral, Sebastian; Castillo, Rolando; Gaspar, Pablo A.; Bustamante, M. Leonor; Silva, Hernan (Frontiers in Psychiatry, 2021)
Brain Derived Neurotrophic Factor (BDNF) has been linked to cognitive symptoms of schizophrenia, which has been documented in previous reviews by several authors. However, a trend has recently emerged in this field moving from studying schizophrenia as a disease to studying psychosis as a group. This review article focuses on recent BDNF studies in relation to cognition in human subjects during different stages of the psychotic process, including subjects at high risk of developing psychosis, patients at their first episode of psychosis, and patients with chronic schizophrenia. We aim to provide an update of BDNF as a biomarker of cognitive function on human subjects with schizophrenia or earlier stages of psychosis, covering new trends, controversies, current research gaps, and suggest potential future developments in the field. We found that most of current research regarding BDNF and cognitive symptoms in psychosis is done around schizophrenia as a disease. Therefore, it is necessary to expand the study of the relationship between BDNF and cognitive symptoms to psychotic illnesses of different stages and origins.